2010
DOI: 10.1590/s0100-204x2010000900008
|View full text |Cite
|
Sign up to set email alerts
|

Proteínas del gluten y reología de trigos harineros mexicanos influeciados por factores ambientales y genotípicos

Abstract: Resumen -El objetivo de este estudio fue conocer el efecto de factores ambientales y genotípicos sobre los parámetros de calidad industrial y sobre la cantidad y relación de proteínas monoméricas y poliméricas del gluten en 24 líneas recombinantes de trigos harineros de temporal. El cultivo se desarrolló en cinco condiciones ambientales generadas por manejo agronómico, ciclo otoño-invierno 2006/2007, en Roque, Guanajuato, México. Se evaluaron el tiempo de amasado (TMA), fuerza (ALVW), extensibilidad (ALVPL) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…A força do glúten (W), expressa em 10 -4 Joules, representa o trabalho (energia) de deformação da massa, que é indicativo da força de panificação da farinha (Módenes et al, 2009). A força de panificação é associada à maior ou à menor capacidade de absorção de água pelas proteínas formadoras do glúten, combinadas à capacidade de retenção do gás carbônico (Olán et al, 2010).…”
Section: Introductionunclassified
“…A força do glúten (W), expressa em 10 -4 Joules, representa o trabalho (energia) de deformação da massa, que é indicativo da força de panificação da farinha (Módenes et al, 2009). A força de panificação é associada à maior ou à menor capacidade de absorção de água pelas proteínas formadoras do glúten, combinadas à capacidade de retenção do gás carbônico (Olán et al, 2010).…”
Section: Introductionunclassified
“…(2016), who reported that the strength of the gluten (reflected in this case by W and the P/L ratio) is affected by rainfall, relative humidity and temperature. Dough baking strength and P/L would be primarily controlled by the environmental conditions (Kaya & Sahin, 2015 ), although according to the current results, the genotype × environment interaction would also have significant effects (De la O Olán et al., 2010). In that sense, medium heritability coefficients have been reported for W and P, whereas L and PROT have been associated to a low heritability (Branlard et al., 2001).…”
Section: Discussionmentioning
confidence: 50%